2015
DOI: 10.1007/s00253-015-6828-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation strategies for removal of residual atrazine in the boreal groundwater zone

Abstract: Strategies for bioremediation of atrazine, a pesticide commonly polluting groundwater in low concentrations, were studied in two boreal nonagricultural soils. Atrazine was not mineralized in soil without bioremediation treatments. In biostimulation treatment with molasses, up to 52% of atrazine was mineralized at 10 °C, even though the degradation gene copy numbers did not increase. Incubations with radioactively labeled atrazine followed by microautoradiographic analysis revealed that bioremediation strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“… In this study, B. atrophaeus YQJ‐6, which can degrade atrazine, was isolated from soil. The optimal pH value and temperature for strain YQJ‐6 to grow and degrade atrazine were 7.0–7.5 and 30–40°C, respectively. The strain YQJ‐6 also had high tolerance to atrazine. The strain YQJ‐6 could tolerate at least 1000 mg/L atrazine under the experimental conditions. The degradation rate of atrazine (50 mg/L) by strain YQJ‐6 reached approximately 99.2% in 7 days. In addition, the strain YQJ‐6 was successfully made into a microbial agent that is easy to commercialize and can be used to treat atrazine residues in soil. The microbial agent containing strain YQJ‐6 achieved good results in this experiment. The addition of atrazine‐degrading bacteria is considered a powerful tool to remediate contaminated soil (Nousiainen et al , 2015). These results suggest that strain YQJ‐6 can be used for the control of atrazine pollution. …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“… In this study, B. atrophaeus YQJ‐6, which can degrade atrazine, was isolated from soil. The optimal pH value and temperature for strain YQJ‐6 to grow and degrade atrazine were 7.0–7.5 and 30–40°C, respectively. The strain YQJ‐6 also had high tolerance to atrazine. The strain YQJ‐6 could tolerate at least 1000 mg/L atrazine under the experimental conditions. The degradation rate of atrazine (50 mg/L) by strain YQJ‐6 reached approximately 99.2% in 7 days. In addition, the strain YQJ‐6 was successfully made into a microbial agent that is easy to commercialize and can be used to treat atrazine residues in soil. The microbial agent containing strain YQJ‐6 achieved good results in this experiment. The addition of atrazine‐degrading bacteria is considered a powerful tool to remediate contaminated soil (Nousiainen et al , 2015). These results suggest that strain YQJ‐6 can be used for the control of atrazine pollution. …”
Section: Resultsmentioning
confidence: 82%
“…Microbial remediation techniques have become a popular alternative to chemical or physical remediation because of their relatively low cost and minimal impact on the environment (Rehan et al , 2014; Nousiainen et al , 2015). However, this approach requires obtaining highly efficient pure strains or microbial consortium with proven application methods (Chirnside et al ., 2010; Sagarkar et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the control group without a microbial agent (Figure 9), the degradation efficiency of atrazine was 29.8% after 7 days, which was attributed to the action of natural microbes, degrading enzymes, and other factors in the soil. Therefore, it was considered that the addition of atrazine-degrading bacteria is a powerful tool to remediate contaminated soil [30]. Although the effect of microbial agents on the treatment of atrazine residues in deep soil was not good enough, the application of microbial agents at the appropriate time after the use of atrazine would effectively reduce its transfer to deep soil [12,30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Neighboring surface water is more liable to contamination when pesticides are applied to highly erodible soils or to over-irrigated or rainsoaked fields. Studies examining the leaching of pesticide were conducted both in field and laboratory scale using packed soil column and the result from the studies revealed that pesticides leach out through the root zone and the leaching process is control by may processes like physical chemical and biological parameters of the pesticide and soil and volume of rainfall events after the use of the pesticide (Nousiainen et al, 2015 andMingorance &Pena, 2014) (Figure 1).…”
Section: Leaching Through Soil Profilementioning
confidence: 99%